1999
DOI: 10.1095/biolreprod61.6.1506
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Presence of Tumor Necrosis Factor Alpha Receptors During Ovarian Development in the Rat1

Abstract: Tumor necrosis factor alpha (TNFalpha) is an intraovarian cytokine that may play a role in ovarian development and function. Effects of TNFalpha are mediated by binding to at least one of two TNFalpha receptor subtypes (with molecular masses of approximately 60 and 80 kDa); therefore, the overall goal of this study was to determine whether rat ovaries have TNFalpha receptors during critical times in development. Two approaches were used: 1) demonstration of specific binding of radiolabeled TNFalpha to ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…ries, we have chosen this receptor type for our study. The positive immunological signal of the TNFR I in the GCs of sows confirms that TNF effects on follicular development and differentiation are due to a receptor-mediated pathway that has already been shown in rat [19], sow [23], and mouse [24].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…ries, we have chosen this receptor type for our study. The positive immunological signal of the TNFR I in the GCs of sows confirms that TNF effects on follicular development and differentiation are due to a receptor-mediated pathway that has already been shown in rat [19], sow [23], and mouse [24].…”
Section: Discussionsupporting
confidence: 78%
“…The role of TNFR II is less understood and has been shown to be more restricted to hematopoetic cells [18]. A recent study on TNFR during ovarian development confirmed the prevalence of TNFR I in rat GCs [19]. Here we asked whether TNFR I in porcine GCs is influenced by its ligand.…”
Section: Introductionmentioning
confidence: 98%
“…1). While both receptor types are expressed in rat ovaries as early as Embryonic Day 19 [21], their localization has not been reported.…”
Section: Discussionmentioning
confidence: 96%
“…TNF immunoreactivity is observed in oocytes in neonatal rats, as well as in oocytes of all follicle stages in adult rat ovaries [20]. Additionally, both of its receptor types are present in rat ovaries beginning at Embryonic Day 19 [21]. To our knowledge, TNF receptor expression in neonatal mouse ovaries has not been reported.…”
Section: Introductionmentioning
confidence: 83%
“…Likewise, TNFα receptors are present on granulosa and theca cells [21,24,27]. From a functional standpoint, TNFα has been shown to inhibit follicle stimulating hormone (FSH)-, insulin-or insulin-like growth factor-I (IGF)-induced estradiol-17β (E2) production in granulosa cells [21,28] and luteinizing hormone (LH)-stimulated androstenedione production in theca cells [28].…”
Section: Tnfα In Follicular Development and Luteal Formationmentioning
confidence: 99%